Comparing clinical characteristics of systemic sclerosis with or without interstitial lung disease: A cross-sectional study from a single center of the Chinese Rheumatism Data Center - Li, Haoguang; Zhang, Xiuling; Yu, Le; Shang, Jingjing; Fan, Jie; Feng, Xueqin; Zhang, Rongwei; Ren, Jie; Guo, Qifang; Duan, Xinwang (Frontiers in Medicine, 2022)
Background We aimed to compare the clinical characteristics of patients with systemic sclerosis (SSc) with or without interstitial lung disease (ILD) to identify relationships with the presence of ILD in SSc at a single center in China. Methods A cross-sectional study was conducted using retrospective data from the Chinese Rheumatology Data Center. Patients diagnosed with SSc at the Second Affiliated Hospital of Nanchang University between 2013 and 2022 were included. Demographic and clinical characteristics were compared between patients with SSc with and without ILD. Logistic regression analyses were performed to explore these associations. Results A total of 227 patients with SSc were included (male:female ratio = 1:4.82), of which 121 (53.3%) were accompanied with ILD. SSc patients with ILD had a higher percentage of diffuse cutaneous systemic sclerosis (dcSSc), sclerodactyly, loss of finger pad, muscle involvement, left ventricular diastolic dysfunction (LVDD), and pulmonary hypertension (PAH), elevated Krebs von den Lungen-6 (KL-6), and elevated ferritin than those without ILD, and a higher modified Rodnan skin score (mRSS), neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) (all P < 0.05). Antinuclear antibody (ANA) and anti-scleroderma-70 (anti-Scl-70) positivity was presented frequently in SSc patients with ILD, while SSc patients without ILD were more often anti-centromere antibody (ACA) positive (all P < 0.05). On the multivariable analysis, muscle involvement [OR 2.551 (95% CI 1.054–6.175), P = 0.038], LVDD [OR 2.360 (95% CI 1.277–4.361), P = 0.006], PAH [OR 9.134 (95% CI 2.335–35.730), P = 0.001], dcSSc [OR 2.859 (95% CI 1.489–5.487), P = 0.002], PLR [OR 1.005 (95% CI 1.001–1.008), P = 0.020], elevated KL-6 [OR 2.033 (95% CI 1.099–3.763), P = 0.024], and anti-Scl-70 [OR 3.101 (95% CI 1.647–5.840), P < 0.001] were statistically significant associations with SSc patients with ILD. Conclusion Systemic sclerosis was found mainly in females. Several important differences in clinical and laboratory characteristics have been demonstrated between SSc patients with or without ILD. Muscle involvement, LVDD, PAH, dcSSc, PLR, elevated KL-6, and Anti-Scl-70 antibody may be associated with SSc in patients with ILD.